2019
DOI: 10.1017/s1754470x18000235
|View full text |Cite
|
Sign up to set email alerts
|

Applying dialectical behaviour therapy to structural and internalized stigma with LGBTQ+ clients

Abstract: Delivering research-supported intervention is increasingly important, given the growing emphasis on evidence-based practice in mental health treatment. When working with clients who hold marginalized identities, however, therapists may have questions about how to best tailor interventions, as treatments may not yet have demonstrated efficacy with under-represented populations. This paper describes potential strategies for using dialectical behaviour therapy (DBT) skills to help LGBTQ+ clients, guided by a theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…This trend was reflected in the DBT RCT samples; for example, the percentage of participants identifying as member of a sexual minority group was particularly high in the two RCTs conducted with samples consisting of young adult college students from the Millennial generation (31.7–38.7%; Pistorello et al, 2012, 2017). Overall, these results indicate that the findings of DBT RCTs are applicable to sexual minority groups and suggest that individuals from sexual minority groups may be more likely to have the types of problems typically treated in DBT (e.g., self-injurious behaviors, and BPD), perhaps due to experiencing frequent environmental invalidation (Skerven et al, 2019). Alternatively, clinicians may diagnose sexual minority individuals with BPD more often than heterosexual individuals (Rodriguez-Seijas et al, 2021).…”
Section: Discussionmentioning
confidence: 79%
“…This trend was reflected in the DBT RCT samples; for example, the percentage of participants identifying as member of a sexual minority group was particularly high in the two RCTs conducted with samples consisting of young adult college students from the Millennial generation (31.7–38.7%; Pistorello et al, 2012, 2017). Overall, these results indicate that the findings of DBT RCTs are applicable to sexual minority groups and suggest that individuals from sexual minority groups may be more likely to have the types of problems typically treated in DBT (e.g., self-injurious behaviors, and BPD), perhaps due to experiencing frequent environmental invalidation (Skerven et al, 2019). Alternatively, clinicians may diagnose sexual minority individuals with BPD more often than heterosexual individuals (Rodriguez-Seijas et al, 2021).…”
Section: Discussionmentioning
confidence: 79%
“…For example, some SOCE participants reported an increase in hopefulness (Shidlo & Schroeder, 2002). However, Skerven, Whicker, and LeMaire (2019) outline the ways in which dialectical behavior therapy (DBT) can be used with LGBQ clients and note that increasing hopefulness is a primary target of DBT. Shidlo and Schroeder (2002) also reported that some participants were able to find effective coping strategies through SOCE.…”
Section: Alternative Therapeutic Methodsmentioning
confidence: 99%
“…“Stage I” DBT, which focuses on treating life-threatening, treatment-interfering, and significant quality of life-interfering behaviors, has a great deal of empirical support for the management of high-risk problems, including suicidality, NSSI, substance use, and disordered eating (Landes & Linehan, 2012). However, DBT was not created to treat minority stress or the effects of social oppression; though more work is emerging in this area (see Cohen et al, 2021; Skerven et al, 2019; Sloan et al, 2017), further research is needed on the efficacy of DBT for minority stress.…”
Section: Discussionmentioning
confidence: 99%